Multilayer oxide ceramic body with suitable sintering behavior

JP2025032023AInactive Publication Date: 2025-03-07IVOCLAR VIVADENT AG
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2024232805
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2016-12-23
Filing Date
2024-12-27
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0030】 したがって本発明の目的は、多層酸化物セラミック体、特に、熱稠密化中に歪みを示さない、異なるように着色された層を有する酸化物セラミックブランクを提供することであり、特に、高い嵌合精度、信頼性、および歯科技工士による加工の容易さ、ならびに最終的に稠密化されたセラミックの非常に良好な美的外観を有する、歯科製品の生成に適したセラミック体を提供することである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032023000001_ABST
    Figure 2025032023000001_ABST
Patent Text Reader

Abstract

To provide multilayer oxide ceramic bodies suitable for dental applications.SOLUTION: The invention relates to multilayer oxide ceramic bodies, in particular, presintered multilayer oxide ceramic blanks and oxide ceramic green bodies, which comprise at least two different layers and are suitable for dental applications, where at least one layer contains La2O3 and the at least two different layers differ in their content of La2O3. These bodies can be thermally densified by further sintering without distortion and are therefore particularly suitable for production of dental restorations. The invention also relates to a process for production of such multilayer oxide ceramic bodies, and to a process for production of dental restorations using the multilayer oxide ceramic bodies.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to multilayer oxide ceramic bodies suitable for dental applications, in particular pre-sintered multilayer oxide ceramic blanks and oxide ceramic green bodies. These bodies can be thermally densified by further sintering without distortion and are therefore particularly suitable for the production of dental restorations with excellent mechanical properties and very high fitting accuracy, making it possible to very closely mimic the optical properties of natural teeth. The present invention also relates to a process for producing such a multilayer oxide ceramic body, as well as a process for producing dental restorations using the multilayer oxide ceramic body. [Background technology]

[0002] For many years, oxide ceramic materials have been used to produce dental implants and restorations. Such ceramics are typically based on zirconia in the form of tetragonal zirconia polycrystal (TZP). Pure ZrO 2 below 950 °C, undergoes a tetragonal to monoclinic phase transition accompanied by a significant increase in volume. For zirconia to remain in its tetragonal form at room temperature, Y 2 O 3 , CEO 2The use of additives such as MgO, MgO, or CaO is necessary. These additives block the tetragonal to monoclinic transformation, thereby resulting in a metastable state in which zirconia is completely or partially in its tetragonal form. If a crack forms in such a metastable tetragonal zirconia ceramic, the stress at the crack tip induces a local transformation from the tetragonal to the monoclinic form, and the accompanying volume increase effectively opposes the crack propagation. This so-called transformation toughening mechanism results in the high toughness of stabilized zirconia ceramics (Hannink et al., J. Am. Ceram. Soc. 2000, Vol. 83, pp. 461-487). This, combined with the bioinert properties of zirconia, has led to the use of doped TZP in orthopedics and for dental restorations. Today, in particular, doping with Al, usually 2 O 3 (about 0.25 wt%), Y 2 O 3 Tetragonal zirconia polycrystals stabilized with yttrium (Y-TZP) are widely used as all-ceramic dental biomaterials (Denry et al., Dental Materials 2008, Vol. 24, pp. 299-307).

[0003] Various processes for preparing ceramics are known, with the preferred processes being (i) axial or cold isostatic pressing (CIP) followed by conventional sintering, (ii) slip casting followed by conventional sintering, and (iii) hot pressing (HP) or hot isostatic pressing (HIP).

[0004] In dental applications, the preparation of ceramic materials often involves two densification steps separated by a molding step. Thus, the ceramic material can be pressed or cast and then pre-sintered to an intermediate open pore state. Molding or pre-forming of the ceramic material can then be performed, followed by final thermal densification by further sintering.

[0005] In order to improve the aesthetic appearance of dental restorations, ceramics used as dental restorative materials often need to be stained. Various possibilities are known for staining ceramic materials.

[0006] One approach to obtain colored dental ceramic materials uses coloring of ceramic materials in a porous state by infiltration with a solution of metal compounds. Typically, the porous structure is dried, fully or partially infiltrated with a coloring solution, the surface is cleaned, the infiltrated structure is dried, the porous structure is optionally infiltrated with additional coloring solution, and finally sintered.

[0007] US 6,709,694 B1 describes a process for the coloring of oxide ceramics in a porous or absorbent state with solutions of salts or complexes of transition metals.

[0008] EP1486476A1 describes a method for producing a metal salt, a solvent, and a M n A process is described for coloring presintered ceramic bodies using a solution containing polyethylene glycol having a molecular weight in the range of 1,000 to 200,000.

[0009] This approach suffers from a complicated process for the dental technician and a low homogeneity of the obtained color distribution. Moreover, depending on the concentration of the coloring ions, the enlargement factor may vary within the colored layer, which leads to stress between the colored and non-colored areas during the final sintering step.

[0010] Another approach involves pre-coloring the zirconia powder by co-precipitation of the zirconia with a coloring compound or by contacting the zirconia powder with a solution of a coloring compound to obtain pre-colored primary and secondary particles with different powder characteristics.

[0011] No. 5,011,403A describes the production of colored brackets by compressing and sintering the powder obtained by adding a colored transition metal oxide to a partially stabilized zirconia powder, where the transition metal oxide is incorporated in powder form or by spraying a solution of a water-soluble salt of the transition metal oxide onto the zirconia powder.

[0012] No. 5,263,858 A describes the production of ivory-colored sintered zirconia bodies that can be used as brackets in orthodontic applications, in which a mixed powder is prepared by (A) co-precipitation and calcination of a solution containing a zirconium compound, a stabilizer, erbium, and praseodymium, or (B) mixing a solution of erbium and praseodymium compounds with a zirconia powder containing a stabilizer, and a compact is formed from the resulting powder and sintered.

[0013] No. 5,656,564A describes a colored sintered zirconia body for orthodontic bracket material produced by wet mixing stabilized zirconia powder with a coloring substance, and molding and sintering the resulting powder.

[0014] US 6,713,421 A describes a blank based on a ceramic composition containing zirconia and at least one of the oxides of aluminum, gallium, germanium and indium, and further coloring additives. The ceramic composition is prepared by coprecipitation and calcination.

[0015] A further approach involves the colouring of ready-to-press ceramic powders by coating techniques.

[0016] US 2007 / 292597 A1 describes a process for producing monochromatic and multi-chromatic blanks and dental molded parts, in which an oxide powder is coated with a coloring substance, the colored powder is compressed to form a molded body, and the compressed body is sintered.

[0017] US 2008 / 0274440 A1 describes an abutment for a dental implant, comprising a one-piece support structure for a dental prosthesis, made from a ceramic material and colored to match the color of the dental prosthesis to the surrounding tooth material and gingival tissue. Coloring of the abutment can be achieved, according to US 2007 / 292597 A1, inter alia, by coating an oxide powder with a coloring substance.

[0018] Yet another technique involves coloring by mixing colored and uncolored powders and pigments together.

[0019] US 6,379,593 describes a process for producing multi-colored bodies suitable for further processing to form dental restorations, in which differently colored ceramic materials are introduced successively into an extrusion die, compressed into the shape of a body, and sintered.

[0020] US 2007 / 272120 A1 describes a ceramic block comprising first and second ceramic compounds having different optical properties and further comprising a transition region between the ceramic compounds where the resulting gradient of variation in the optical properties is substantially constant.

[0021] US 2008 / 064011 A1 describes a multi-colored molded body having differently colored main and intermediate layers, where the color change between the intermediate layers occurs in a direction opposite to the direction of the color change between the main layers. Multi-colored molded bodies are also disclosed having differently colored main layers and intermediate layers that contain a mixture of the materials of the main layers.

[0022] WO2008 / 083358A1 describes a multi-coloured dental blank having concentric inner and outer zones of different colouration.

[0023] US2010 / 0216095A1 describes the production of colored dental ceramics in which Y-TZP is mixed with a coloring component to obtain a substantially homogeneous agglomerate material, and the differently colored agglomerates are mixed, pressed and sintered.

[0024] US2011 / 0189636A1 describes a molded body containing differently colored first and second components, where the second component is disposed within the first component such that a curved interface is formed.

[0025] US 2012 / 139141 A1 describes the production of a colored zirconia product by treating a Y-TZP powder with a solution of a colorant to obtain a pigment powder, mixing the pigment powder with an uncolored powder, compressing the mixed powder and sintering it.

[0026] It has been shown that state-of-the-art processes suffer from different and incompatible sintering kinetics of the various ceramic powders used therein (e.g., combinations of pigmented and non-pigmented powders, or combinations of differently pigmented powders, etc.). When different powders are combined to form different layers of a multi-layer ceramic body, the difference in these sintering kinetics leads to distortion of the multi-layer ceramic body upon sintering. Such distortion is undesirable, especially for dental applications.

[0027] WO2015 / 011079A1 describes a multilayer oxide ceramic blank for producing dental restorations and a process for producing the same, in which the sintering behavior of the different layers is matched. However, in order to mimic the properties of natural teeth, It has been shown that the colour, and especially the translucency properties, of these oxide ceramics are not optimal in all cases. [Prior art documents] [Patent documents]

[0028] [Patent Document 1] U.S. Patent No. 6,709,694 [Patent Document 2] European Patent Application Publication No. 1486476 [Patent Document 3] U.S. Pat. No. 5,011,403 [Patent Document 4] U.S. Pat. No. 5,263,858 [Patent Document 5] U.S. Pat. No. 5,656,564 [Patent Document 6] U.S. Patent No. 6,713,421 [Patent Document 7] US Patent Application Publication No. 2007 / 292597 [Patent Document 8] US Patent No. 2008 / 0274440 [Patent Document 9] U.S. Patent No. 6,379,593 [Patent Document 10] US Patent Application Publication No. 2007 / 272120 [Patent Document 11] US Patent Application Publication No. 2008 / 064011 [Patent Document 12] International Publication No. 2008 / 083358 [Patent Document 13] US Patent Application Publication No. 2010 / 0216095 [Patent Document 14] US Patent Application Publication No. 2011 / 0189636 [Patent Document 15] US Patent Application Publication No. 2012 / 139141 [Non-patent literature]

[0029] [Non-Patent Document 1] Hannink et al., J. Am. Ceram. Soc. 2000, 83, 461-487 [Non-Patent Document 2] Denry et al., Dental Materials 2008, Vol. 24, pp. 299-307 Summary of the Invention [Means for solving the problem]

[0030] The object of the present invention is therefore to provide a multilayer oxide ceramic body, in particular an oxide ceramic blank with differently colored layers, which does not show distortion during thermal densification, and in particular to provide a ceramic body suitable for the production of dental products, having high fitting precision, reliability and ease of processing by the dental technician, as well as a very good aesthetic appearance of the final densified ceramic.

[0031] This object is achieved by a pre-sintered multilayer oxide ceramic blank according to claims 1 to 17 and 20. The subject of the invention is also a process for producing a multilayer oxide ceramic green body according to claims 18 to 20, a blank or green body according to claims 21 to 24 and a multilayer oxide ceramic blank or green body obtainable by this process according to claim 25, as well as a process for producing a dental restoration according to claims 26 to 29.

[0032] The pre-sintered multi-layer oxide ceramic blank according to the present invention is characterized in that it has at least two different layers, at least one of which is La 2 O 3 and the at least two different layers contain those La 2 O 3 It is characterized by comprising at least two different layers that differ in content.

[0033] Surprisingly, it has been shown that the blanks according to the invention show no or essentially no distortion during pre-sintering or final sintering. In particular, these blanks do not suffer from significant differences in the sintering kinetics or shrinkage behavior between the different layers. Surprisingly, La 2 O 3It has been found that the addition of La is particularly suitable for adjusting the sintering behavior of the different layers. 2 O 3 The addition of makes it possible to compensate for the different sintering behavior caused by different properties of the starting powders, such as the BET specific surface area, grain size, grain shape, pressing behavior and chemical composition of the powder, in particular the additives for improving the color and translucency properties.

[0034] According to the invention, at least one layer contains 0.005 to 5 wt%, in particular 0.01 to 1.0 wt%, preferably 0.025 to 0.5 wt%, most preferably 0.03 to 0. 20wt% La 2 O 3 A blank containing

[0035] In addition, at least one layer is Al 2 O 3 Blanks containing Al and / or MgO are preferred. 2 O 3 and MgO.

[0036] At least one layer contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.10 wt% Al. 2 O 3 and / or MgO-containing blanks are preferred.

[0037] In particular, at least one layer contains 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.10 wt%, most preferably 0.02 to 0.05 wt% Al. 2 O 3 Likewise preferred are blanks in which at least one layer contains 0.001 to 5 wt. %, in particular 0.005 to 1.0 wt. %, preferably 0.01 to 0.10 wt. %, most preferably 0.01 to 0.03 wt. % MgO.

[0038] In addition, at least one layer is made of Al 2 O 3 and MgO in a weight ratio of 10:1 to 1:10, preferably 5:1 to 1:1, particularly preferably 4:1 to 2:1.

[0039] At least one layer is La 2 O 3 in the amounts especially defined above, and at least one other layer contains Al 2 O 3 and / or MgO, especially in the amounts defined above, are particularly preferred.

[0040] In a preferred embodiment, at least one layer, preferably all layers, of the blank according to the invention comprises Y 2 O 3 At least one layer, preferably all layers, contains 0.1 to 20.0 wt %, in particular 1.0 to 15.0 wt %, preferably 5.0 to 12.5 wt %, most preferably 7.0 to 9.5 wt % Y. 2 O 3 It is preferable that Y 2 O 3 The addition of Y has been shown to be particularly suitable for imparting to the blank and the dental product produced therefrom a color, in particular a translucent property, which can particularly well mimic the corresponding properties of natural tooth material. Furthermore, the at least two different layers have their Y 2 O 3 It is preferable that they differ in content. 2 O 3 Layer with highest Y content 2 O 3 Between the layers with Y content 2 O 3It is particularly preferred that the difference in content is at least 1.0 wt%, preferably at least 1.5 wt%, in particular at least 1.8 wt%, more preferably at least 2.0 wt%, in particular at least 2.5 wt%, even more preferably at least 3.0 wt%, in particular at least 3.5 wt% and most preferably at least 3.8 wt%.

[0041] According to the present invention, the minimum Y 2 O 3 The layer containing La 2 O 3 Contains and / or the highest Y 2 O 3 The layer containing Al 2 O 3 and / or MgO. 2 O 3 La content in layers 2 O 3 On the other hand, the use of high Y 2 O 3 Al content in layers 2 O 3 and / or the use of MgO, Y 2 O 3 It has been unexpectedly shown that the method is particularly suitable for adjusting the sintering behavior of layers having different amounts of

[0042] The lowest Y 2 O 3 The layer having a La content of 0.005 to 5 wt%, in particular 0.01 to 1.0 wt%, preferably 0.25 to 0.09 wt%, most preferably 0.5 to 0.8 wt%. 2 O 3 It is particularly preferred that the highest Y 2 O 3 The layer has a content of 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.10 wt% Al. 2 O 3 and / or MgO It is even more preferred that it contains

[0043] In a particularly preferred embodiment of the blank according to the invention, the La 2 O 3 The weight ratio is given by the following formula: m(La 2 O 3 )=m min (La 2 O 3 )+(m max (Y 2 O 3 )-m(Y 2 O 3 ))×f It is calculated by During the ceremony, m(La 2 O 3 ) is the La 2 O 3 is the percentage by weight of m min (La 2 O 3 ) is the La of all layers 2 O 3 is a minimum percentage by weight of m(Y 2 O 3 ) is the Y 2 O 3 is the percentage by weight of m max (Y 2 O 3 ) is the Y 2 O 3 is the maximum percentage by weight of f is in the range of 0.01 to 1.00, in particular in the range of 0.03 to 0.20, preferably in the range of 0.06 to 0.10, particularly preferably in the range of 0.065 to 0.085, most preferably in the range of 0.081 to 0.083.

[0044] Oxide ceramics are generally highly crystalline ceramic materials based on oxide compounds and contain, at most, a very low percentage of glass phase. Typical oxide ceramics are ZrO 2 , Al 2 O 3 , TiO 2, MgO, combinations, solid solutions, and complexes of these. 2 and / or Al 2 O 3 Oxide ceramics based on are particularly preferred.

[0045] Zirconia-based, in particular, e.g. Y 2 O 3 , CEO 2 Oxide ceramics based on tetragonal zirconia polycrystals (TZP), suitably stabilized with yttria, MgO and / or CaO, are particularly preferred. Particularly preferred oxide ceramics are yttria-stabilized tetragonal zirconia polycrystals (Y-TZP), cerium oxide-stabilized tetragonal zirconia polycrystals (Ce-TZP), zirconia-toughened alumina (ZTA) and alumina-toughened zirconia (ATZ).

[0046] ZrO in zirconia-based oxide ceramics 2 , Y 2 O 3 , and HfO 2 It is particularly preferred that the total amount of is at least 99.0 wt %. It is further preferred that the zirconia-based oxide ceramic contains the following components in the amounts indicated: Y 2 O 3 2.0 to 10.0 wt%, in particular 4.5 to 6.0 wt%, HfO 2 Maximum 5.0wt%, Al 2 O 3 Up to 5.0wt%, especially up to 0.5wt%, SiO 2 up to 0.1 wt.%, and Na 2 O 0.1 wt% max.

[0047] The blank according to the invention is particularly suitable for producing dental products, in particular for producing multi-unit dental restorations. The blank according to the invention is particularly suitable for producing dental restorations, in particular bridges, which include two or more units.

[0048] Different layers of the blank usually have different colors. Within the meaning of this application, the terms "color" and "colored" refer to the color, brightness and / or color of the layers. or translucency.

[0049] "Translucency" is the light transmitting ability of a material, object, or layer, i.e., the ratio of transmitted light intensity to the incident light intensity.

[0050] The color is L * a * They can also be characterized by b-values ​​or by color codes commonly used in the dental industry. Examples of such color codes are Vitapan classical® and Vita 3D Master®, both from VITA Zahnfabrik H. Rauter GmbH & Co. KG, and Chromascop® from Ivoclar Vivadent AG.

[0051] It is particularly preferred that the colours of the different layers are within the range of natural tooth colours.

[0052] The layers are preferably planar layers arranged parallel to one another. The blank is preferably in the form of a rectangular block, a disk, a cylinder, a dental preform, an abutment preform, a tooth sector, a horseshoe, a cone, a cone segment, a pyramid, a pyramid segment, a torus, a torus segment, a truncated cone, a truncated cone segment, a tube, a tube segment, a sphere, a sphere segment, an ellipse or an ellipse segment, in each case with or without a notch or ledge.

[0053] In a further preferred embodiment, the blank according to the invention has a distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2 and most preferably less than 0.1.

number

number

[0054] The Vickers hardness according to standard ISO 14705:2008 is particularly suitable for predicting the sintering behavior of different regions within a pre-sintered multi-layer blank.

[0055] The calculation of the distortion factor should generally be based on multiple measurements of Vickers hardness at locations encompassing each of the different layers of the blank. It may also be possible to include measurements of Vickers hardness at internal surfaces of the blank that are accessible by cutting the blank into individual segments or discs. It is even more preferred that the measurements encompass a portion of the blank that is at least as large as a typical restoration that will be produced from the blank.

[0056] In one embodiment, the distortion coefficient is calculated based on measurements of HV at measurement points distributed at regular intervals along a first line intersecting different layers of the outer surface of the blank, with additional measurement points distributed at regular intervals along a second line parallel to the first line at the center of the blank and at the surface, preferably accessible by cutting the blank.

[0057] The regular interval between the measurement points along the first and second lines shall be 5 mm or less. It is particularly preferred that the central surface of the blank is made accessible by cutting the blank in half.

[0058] The HV values ​​of pre-sintered ceramic materials for CAD / CAM applications are typically in the range of 300 to 1000 MPa.

[0059] The present invention relates to a multi-layered oxide ceramic green body for producing a dental restoration comprising at least two different layers, at least one of which is La. 2 O 3 and the at least two different layers are 2 O 3 It also relates to a multi-layered oxide ceramic green body, which differs in content.Preferred embodiments of the oxide ceramic green body are as defined above for the oxide ceramic blank according to the invention.

[0060] In a preferred embodiment, the oxide ceramic green body according to the invention has a distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2 and most preferably less than 0.1.

number

number

[0061] In the sintering step, the green body is preferably heated at a heating rate of 1 to 10 K / min, preferably 5 K / min, to a temperature 50 K below the desired sintering temperature, and at 1 to 3 K / min, preferably 1 K / min, to the desired sintering temperature, preferably about 1100° C., and maintained at this temperature for 30 to 480 minutes, preferably 120 to 180 minutes. In a particular embodiment, the green body is heated at a heating rate of 5 K / min to a temperature 50 K below the desired sintering temperature, and at 1 K / min to the desired sintering temperature, preferably about 1100° C., and maintained at this temperature for 120 minutes. If the green body contains a binder, the sintering step is typically preceded by a debinding step, which comprises heating to 300° C., 500° C. or 700° C. at a heating rate of 0.1 to 0.5 K / min, preferably 0.1 to 0.3 K / min, more preferably 0.25 K / min, with a holding time of 20 to 120 minutes, preferably 60 minutes, at 300° C. and / or 500° C. and / or 700° C. In certain embodiments, the debinding step is The steps included heating to 700°C at a heating rate of 0.25 K / min with hold times of 300°C, 500°C, and 60 min at 700°C.

[0062] Within the meaning of this application, the term "green body" generally refers to an unsintered ceramic material, typically produced by densification, such as compaction, of oxide ceramic powders. Pertaining to the body.

[0063] The sintering behavior of the at least two different layers of the blank according to the invention or of the green body according to the invention is preferably adjusted so that the blank or green body can be sintered without distortion.

[0064] Furthermore, the present invention relates to a process for producing the blank according to the invention and the green body according to the invention, said process comprising the steps of: (a) providing at least one first oxide ceramic material and one second oxide ceramic material, the at least one first oxide ceramic material and the one second oxide ceramic material differing with respect to their chemical composition; (b)La 2 O 3 is added to at least one of the oxide ceramic materials; and (c) optionally, Al 2 O 3 and / or MgO is added to at least one of the oxide ceramic materials. It is characterized by:

[0065] At least one of the oxide ceramic materials, and preferably both oxide ceramic materials, is Y 2 O 3 In this case, the first oxide ceramic material and the second oxide ceramic material preferably contain their Y 2 O 3 It is particularly preferred that they differ in content.

[0066] In a preferred embodiment of the process according to the invention, the at least one oxide ceramic material is 2 O 3 and / or at least one oxide ceramic material is infiltrated with Al. 2 O 3 and / or MgO. Suitable infiltration methods are described, for example, in US 2014 / 135200 A1.

[0067] In another preferred embodiment of the process according to the invention, the at least one oxide ceramic material is La 2 O 3 and / or at least one oxide ceramic material is coated with Al 2 O 3 and / or coated with MgO. Suitable coating methods are described, for example, in US 2007 / 292597 A1.

[0068] According to a further preferred embodiment, the process according to the invention comprises the steps of: (d) forming layers of oxide ceramic material and arranging the layers one on top of the other; (e) the oxide ceramic material is compacted, in particular compressed, with a view to obtaining a green body; and (f) Optionally, the green body is pre-sintered to obtain a pre-sintered ceramic blank. The present invention is further characterized by the following.

[0069] In a particularly preferred embodiment, the layers of oxide ceramic material exhibit a continuous change in composition from the composition of the first oxide ceramic material to the composition of the second oxide ceramic material, which makes it possible to form a continuous color gradient without visible boundaries and transitions between the individual layers.

[0070] Finally, the present invention also relates to a multilayer oxide ceramic blank or green body obtainable by the process according to the invention. Preferred embodiments of the oxide ceramic blank or green body are as described above for the oxide ceramic blank according to the invention.

[0071] The multilayer oxide ceramic body according to the invention is particularly suitable for producing dental restorations. The invention therefore also relates to a process for producing dental restorations, in which a blank according to the invention or a green body according to the invention is used.

[0072] In the process for producing a dental restoration, the multilayer oxide ceramic body is preferably given a desired geometric shape in order to obtain a shaped ceramic product. The shaping is preferably performed by machining. The machining is typically controlled by a computer, preferably using a CAD / CAM process.

[0073] In a preferred embodiment, the molded ceramic product has the shape of a dental framework or abutment, or a monolithic fully anatomical dental restoration, especially a multi-unit dental restoration. It is further preferred that the shaped ceramic article be densely sintered. [Brief description of the drawings]

[0074] [Figure 1] The results, described below, are shown in Figure 1A (overview) and 1B (detailed view). [Diagram 2] The results, described below, are shown in Figure 2A (overview) and 2B (detailed view). [Diagram 3] The results, described below, are shown in Figure 3A (overview) and 3B (detailed view). [Figure 4] The results, described below, are shown in Figure 4A (overview) and 4B (detailed view). [Diagram 5] The results, described below, are shown in Figure 5A (overview) and 5B (detailed view). [Figure 6]The results, described below, are shown in Figures 6A (overview) and 6B (detailed view). [Figure 7] The results, described below, are shown in FIG. 7 (debindered and presintered blank) and FIG. 8 (densely sintered blank in transmitted light). [Figure 8] The results, described below, are shown in FIG. 7 (debindered and presintered blank) and FIG. 8 (densely sintered blank in transmitted light). [Figure 9] The results, described below, are shown in Figures 9A (overview) and 9B (detailed view). [Figure 10] The results, described below, are shown in Figure 10A (overview) and 10B (detailed view). [Figure 11] The results, described below, are shown in Figures 11A (overview) and 11B (detailed view). [Figure 12] The results, described below, are shown in Figures 12A (overview) and 12B (detailed view). [Figure 13] The results, described below, are shown in Figures 13A (overview) and 13B (detailed view). [Figure 14] The results, described below, are shown in Figures 14A (overview) and 14B (detailed view). [Figure 15] The results, described below, are shown in FIG. [Figure 16] The results, described below, are shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0075] The invention will now be described in more detail with reference to examples. EXAMPLES

[0076] General Process for Treating Oxide Powders with Colorants and / or Dopants The processing of the oxide powders in the following examples was carried out similarly to US 2014 / 135200 A1.

[0077] For this purpose, an aqueous treatment solution was prepared containing an appropriate amount of water-soluble nitrate of the element with which the oxide powder was intended to be treated. An appropriate amount of oxide powder (e.g. 1,000 g) was introduced into the mixing vessel of an "EL1" laboratory mixer (Eirich, Hardheim), which also had an agitator (star agitator) and a spray nozzle (0.3 mm hollow cone) for applying the solution. The mixing vessel was set to move at a speed of 13 m / s, and the oxide powder placed therein was homogeneously agitated by the agitator. Approximately 0.1 g of treatment solution per gram of oxide powder was then introduced into the mixing vessel using a type 120S / DV peristaltic pump (Watson Marc). The oxide powder was sprayed through a spray nozzle with the aid of a 1000 rpm (Rommerskirchen, low speed; speed 170 rpm), thereby allowing the oxide powder to be uniformly infiltrated with the treatment solution.

[0078] Example 1 La 2 O 3 Tuning the sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents by doping with zirconia To prepare the colored zirconia powders, commercially available zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a common process, thereby obtaining powders suitable for the dentin layer (L1) and for the cutting layer (L2). [Table 1] 1) of the total weight of the oxide mixture after sintering 2) 9.25wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 3) 7.37wt% Y 2 O 3and 0.048 wt% Al 2 O 3 Contains 4) Fe 2 O 3 was calculated as 5) Cr 2 O 3 was calculated as 6) Pr 2 O 3 was calculated as 7) Er 2 O 3 was calculated as 8) La 2 O 3 was calculated as

[0079] Then, about 10 g of each of the colored zirconia powders were introduced into the pressing die (diameter about 40 mm) of a laboratory axial press in two layers (L1 at the bottom, L2 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0080] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and presintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). The edge of a paper or ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figure 1A (overview) and 1B (detailed view). The presintered blanks showed negligible bending of only 0.03 mm.

[0081] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0082] Sections of the densely sintered blanks were then measured under the stereomicroscope described above. The results are shown in Figures 2A (overview) and 2B (detailed view). The densely sintered blanks showed no measurable bending.

[0083] Example 2 (comparison) La 2 O 3 Sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents without doping Example 1 was repeated identically, but without the addition of lanthanum as a dopant. The results for the debindered and pre-sintered blanks are shown in Figures 3A (overview) and 3B (detailed). In these figures it can be clearly seen that the dentin layer (L1) has shrunk more than the cutting layer (L2), whereby the blank has acquired a convex shape. The bending of the blank was 0.36 mm. The results after dense sintering of the blanks are shown in Figures 4A (overview) and 4B (detailed). Even the densely sintered blanks still showed a bending of 0.04 mm afterwards.

[0084] Example 3 La 2 O 3 Tuning the sintering behavior of four-layer blanks made of zirconia powders with different yttrium contents by doping with zirconia For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with a solution of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a general process. Thereby, a powder suitable for the dentin layer (L1) and a powder suitable for the cutting layer (L4) were obtained. These powders were further obtained as two powders suitable for the intermediate layer by mixing them in a ratio of 1:2 or 2:1, respectively, using a shaker mixer (Turbula, WAB, Muttenz). [Table 2] 1) of the total weight of the oxide mixture after sintering 2) 9.25wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 3) 7.37wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 4) Fe 2 O 3 was calculated as 5) Cr 2 O 3 was calculated as 6) Pr 2 O 3 was calculated as 7) Er 2 O 3 was calculated as 8) La 2 O 3 was calculated as

[0085] About 19 g of each of the colored zirconia powders were then introduced into a pressurizing die (diameter about 40 mm) of a laboratory axial compressor in four layers (L1 at the bottom, L4 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0086] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A piece of paper or a ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 5A (overview) and 5B (detailed view). The pre-sintered blanks showed negligible bending of only 0.02 mm.

[0087] Furthermore, the Vickers hardness HV 5 The development of was measured on sections of the pre-sintered blanks using a hardness tester (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 1.5 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 3]

[0088] From these values, a distortion coefficient of d=0.114 was calculated.

[0089] Finally, the blanks were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the following firing and cooling program: 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0090] From the densely sintered blank thus obtained, sections of approximately 2 mm thickness were then cut as described above and measured under a stereomicroscope. The results are shown in Figures 6A (overview) and 6B (detailed view). The densely sintered blank showed no measurable bending.

[0091] Example 4 La 2 O 3 Tuning the sintering behavior of four-layer blanks made of zirconia powders with different yttrium contents by doping with zirconia Example 3 was repeated with larger batches. For this purpose, about 115 g of each of the colored zirconia powders obtained as in Example 3 were introduced into the pressing die (diameter about 100 mm) of a powder press in four layers (at the bottom: L1, at the top: L4) one after the other and axially densified under a pressure of about 160 MPa. The blanks were first debindered as described in Example 3, presintered and then densely sintered. Sections with a thickness of about 2 mm in each case were cut from the blanks thus obtained and measured under a stereomicroscope. The results are shown in FIG. 7 (debindered and presintered blanks) and FIG. 8 (densely sintered blanks in transmitted light). The blanks did not show any measurable bending.

[0092] Furthermore, the Vickers hardness HV 5 The development of was measured on sections of the pre-sintered blanks using a hardness tester (ZHU 0.2, Zwick Roell, ulm) at 10 measuring points spaced 2 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 4]

[0093] From these values, a distortion coefficient of d=0.088 was calculated.

[0094] Example 5 La 2 O 3 Tuning the sintering behavior of blanks with continuous color and translucency profiles made of zirconia powders with different yttrium contents by doping with For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH TZ-PX-471 and TOSOH Zpex Smile) were used as raw materials and treated with a solution of nitrates of coloring elements and optionally lanthanum as dopant according to the table below using a general process, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 5] 1) of the total weight of the oxide mixture after sintering 2) 9.25wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 3) 7.37wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 4) Fe 2 O 3 was calculated as 5) Mn 2 O 3 was calculated as 6) Pr 2 O 3 was calculated as 7) Tb 2 O 3 was calculated as 8) Er 2 O 3 was calculated as 9) La 2 O 3 was calculated as

[0095] The colored zirconia powder was then introduced into a pressing die (diameter about 100 mm) of a powder press in the form of a continuous gradient using a suitable packing process and axially densified under a pressure of about 160 MPa. The green body thus obtained was debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0096] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A piece of paper or a ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 9A (overview) and 9B (detailed view). The pre-sintered blanks showed negligible bending of only 0.01 mm.

[0097] Furthermore, the Vickers hardness HV 5 The development of was measured on sections of the presintered blanks using a hardness tester (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 1.5 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 6]

[0098] From these values, a distortion coefficient of d=0.083 was calculated.

[0099] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0100] Sections of the densely sintered blanks were then examined under a stereomicroscope as described above. The results are shown in Figures 10A (overview) and 10B (detailed view). The densely sintered blanks showed no measurable bending.

[0101] Example 6 La 2 O 3 , Al 2 O 3 , and to tailor the sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents by doping with MgO. For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH Zpex and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum or aluminum and magnesium as dopants using a general process according to the table below, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 7] 1) of the total weight of the oxide mixture after sintering 2) 9.25wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 3) 5.36wt% Y 2 O 3and 0.048 wt% Al 2 O 3 Contains 4) Fe 2 O 3 was calculated as 5) Mn 2 O 3 was calculated as 6) Pr 2 O 3 was calculated as 7) Tb 2 O 3 was calculated as 8) Er 2 O 3 was calculated as 9) Al 2 O 3 was calculated as 10) Calculated as MgO 11) La 2 O 3 was calculated as

[0102] Then, about 10 g of each of the colored zirconia powders were introduced into the pressing die (diameter about 40 mm) of a laboratory axial press in two layers (L1 at the bottom, L2 at the top) one after the other and axially densified under a pressure of about 160 MPa. The green bodies thus obtained were debindered and presintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1010°C at 60K / min and hold for 3 hours.

[0103] Sections of approximately 2 mm thickness were cut from the thus obtained debindered and pre-sintered blanks using a saw (IsoMet 4000, Buehler, Esslingen). A ruler was placed on the two lower outer edges of the section as a reference line and the area of ​​maximum bending was measured under a stereomicroscope (SZX 16, Olympus, Hamburg). The results are shown in Figures 11A (overview) and 11B (detailed view). The pre-sintered blanks showed negligible bending of only 0.03 mm.

[0104] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0105] Sections of the densely sintered blanks were again measured under a stereomicroscope as described above. The results are shown in Figures 12A (overview) and 12B (detailed view). The densely sintered blanks showed no measurable bending.

[0106] Example 7 (comparison) La 2 O 3 Sintering behavior of two-layer blanks made of zirconia powders with different yttrium contents and without doping Example 6 was repeated identically, but without the addition of dopants (lanthanum, aluminum, magnesium). The results for the debindered and pre-sintered blanks are shown in Figures 13A (overview) and 13B (detailed view). In these figures it can be clearly seen that the dentin layer (L1) has shrunk more than the cutting layer (L2), whereby the blank has acquired a convex shape. The bending of the blank was 0.74 mm. The results after dense sintering of the blanks are shown in Figures 14A (overview) and 14B (detailed view). It can be seen that even the densely sintered blanks still showed a bending of 0.05 mm.

[0107] Example 6 was repeated in the same manner, but without the addition of dopants (lanthanum, aluminum, magnesium). The results for the debindered and presintered blanks are shown in Figures 13A (overview) and 13B (detailed view).

[0108] Example 8 La 2 O 3 , Al 2 O 3 and to tailor the sintering behavior of blanks with continuous color and translucency gradients made of zirconia powders with different yttrium contents by doping with MgO. For the preparation of colored zirconia powders, commercial zirconia powders (TOSOH Zpex and TOSOH Zpex Smile) were used as raw materials and treated with solutions of nitrates of coloring elements and optionally lanthanum or aluminum and magnesium as dopants using a general process according to the table below, thereby obtaining powders suitable for the dentin layer (L1) and cutting layer (L2). [Table 8] 1) of the total weight of the oxide mixture after sintering 2) 9.25wt% Y 2 O 3 and 0.048 wt% Al 2 O3 Contains 3) 5.36wt% Y 2 O 3 and 0.048 wt% Al 2 O 3 Contains 4) Fe 2 O 3 was calculated as 5) Mn 2 O 3 was calculated as 6) Pr 2 O 3 was calculated as 7) Tb 2 O 3 was calculated as 8) Er 2 O 3 was calculated as 9) Al 2 O 3 was calculated as 10) Calculated as MgO 11) La 2 O 3 was calculated as

[0109] The pigmented zirconia powder was then loaded into a pressing die (diameter about 100 mm) of a powder press in the form of a continuous gradient using a suitable packing process and axially densified at a pressure of about 160 MPa. The green body thus obtained was debindered and pre-sintered using the firing program described below. 60K / min to 120℃, 24K / min to 200℃, 10K / min to 320℃, Bring to 1050°C at 60K / min and hold for 3 hours.

[0110] Sections approximately 2 mm thick were cut from the debindered and presintered blanks thus obtained using a saw (IsoMet 4000, Buehler, Esslingen). The results are shown in Figure 15. The presintered blanks showed negligible bending. I didn't.

[0111] Furthermore, the Vickers hardness HV 5 The development of was measured on sections of the presintered blanks using a hardness tester (ZHU 0.2, Zwick Roell, Ulm) at 10 measuring points spaced 2 mm apart in each case. The determined hardness values ​​are listed in the table below. [Table 9]

[0112] From these values, a distortion coefficient of d=0.22 was calculated.

[0113] Finally, the presintered blank pieces were densely sintered in a Programat S1 furnace (Ivoclar Vivadent AG, Schaan) using the firing and cooling program described below. 600K / h to 900℃, hold for 0.5h, 200K / h to 1500℃, hold for 2 hours, 600K / hour to 900℃, Heat to 300℃ at 500K / hour.

[0114] Sections of the densely sintered blank were again measured under the stereomicroscope as described above, and the results are shown in Figure 16. The densely sintered blank showed negligible bending.

[0115] The present invention provides, for example, the following items. (Item 1) A pre-sintered multi-layer oxide ceramic blank for producing a dental restoration, said blank comprising at least two different layers, at least one layer being La 2 O 3and the at least two different layers are 2 O 3 Pre-sintered multi-layered oxide ceramic blanks differing in content. (Item 2) At least one layer contains 0.005 to 5 wt%, in particular 0.01 to 1.0 wt%, preferably 0.025 to 0.5 wt%, most preferably 0.03 to 0.20 wt% La. 2 O 3 The blank according to item 1, comprising: (Item 3) At least one layer is Al 2 O 3 and / or MgO. (Item 4) At least one layer is La 2 O 3 and at least one other layer is Al 2 O 3 and / or MgO. (Item 5) The at least one layer contains 0.001 to 5 wt. %, in particular 0.005 to 1.0 wt. %, preferably 0.01 to 0.20 wt. %, most preferably 0.02 to 0.10 wt. % Al. 2 O 3 and / or MgO. (Item 6) The at least one layer contains 0.001 to 5 wt. %, in particular 0.005 to 1.0 wt. %, preferably 0.01 to 0.10 wt. %, most preferably 0.02 to 0.05 wt. % Al. 2 O 3 6. The blank according to any one of items 3 to 5, comprising: (Item 7) 7. The blank according to any one of items 3 to 6, wherein the at least one layer comprises 0.001 to 5 wt.%, in particular 0.005 to 1.0 wt.%, preferably 0.01 to 0.10 wt.%, most preferably 0.01 to 0.03 wt.% MgO. (Item 8) The at least one layer is Al 2 O 3 and MgO in a weight ratio of 10:1 to 1:10, preferably 5:1 to 1:1, particularly preferably 4:1 to 2:1. (Item 9) At least one layer, preferably all layers, are 2 O 3 In particular, one or preferably all layers contain 0.1 to 20.0 wt. %, in particular 1.0 to 15.0 wt. %, preferably 5.0 to 12.5 wt. %, most preferably 7.0 to 9.5 wt. % Y 2 O 3 9. The blank according to any one of items 1 to 8, comprising: (Item 10) The at least two different layers have their Y 2 O 3 The Y 2 O 3 Layer with highest Y content 2 O 3 Between the layers with Y content 2 O 3 10. The blank according to item 9, wherein the difference in content is at least 1.0 wt%, preferably at least 1.5 wt%, in particular at least 1.8 wt%, even more preferably at least 2.0 wt%, in particular at least 2.5 wt%, even more preferably at least 3.0 wt%, in particular at least 3.5 wt%, and most preferably at least 3.8 wt%. (Item 11) The lowest Y 2 O 3 The layer has a La content of 0.005 to 5 wt.%, in particular 0.01 to 1.0 wt.%, preferably 0.25 to 0.9 wt.%, most preferably 0.5 to 0.8 wt.%. 2 O 3 The blank according to item 10, comprising: (Item 12) The best Y 2 O 3The layer has a content of 0.001 to 5 wt%, in particular 0.005 to 1.0 wt%, preferably 0.01 to 0.20 wt%, most preferably 0.02 to 0.1 wt% Al. 2 O 3 and / or MgO. (Item 13) In each of the at least two different layers, La 2 O 3 The weight ratio of m(La 2 O 3 )=m min (La 2 O 3 )+(m max (Y 2 O 3 )-m(Y 2 O 3 ))×f It is calculated by During the ceremony, m(La 2 O 3 ) is the La 2 O 3 is the percentage by weight of m min (La 2 O 3 ) is the La of all layers 2 O 3 is a minimum percentage by weight of m(Y 2 O 3 ) is the Y 2 O 3 is the percentage by weight of m max (Y 2 O 3 ) is the Y 2 O 3 is the maximum percentage by weight of f is in the range of 0.01 to 1.00, in particular in the range of 0.03 to 0.20, preferably in the range of 0.06 to 0.10, particularly preferably in the range of 0.065 to 0.085, and most preferably 13. The blank according to any one of items 9 to 12, wherein the .DELTA..times ... (Item 14) 14. The blank according to any one of the preceding claims, wherein the oxide ceramic is based on zirconia, preferably on stabilized tetragonal zirconia polycrystals. (Item 15) 15. The blank according to any one of items 1 to 14, suitable for producing a multi-unit dental restoration, preferably a dental restoration comprising two or more units, in particular a bridge comprising two or more units. (Item 16) 16. The blank of any one of the preceding claims, wherein the at least two different layers have different colors. (Item 17) A distortion coefficient of less than 0.4, in particular less than 0.35, in particular less than 0.3, preferably less than 0.25, even more preferably less than 0.2, most preferably less than 0.1.

number

number

Claims

[Claim 1] The invention as depicted in the drawings.

Citation Information

Patent Citations

  • Uniformly coloured ceramic framework and colouring solution

    EP1486476A1

  • Block and method of making

    US20070272120A1

  • Process for the preparation of colored blanks and dental shaped parts

    US20070292597A1

  • Multi-colored shaped body

    US20080064011A1

  • Dental Implant Abutment

    US20080274440A1